On the Importance to Economic Success of Property Rights in Finance and Innovation - Stephen H. Haber; F. Scott Kieff; Troy A. Paredes (Washington University Journal of Law & Policy, 2008)
This Essay surveys recent developments across the fields of finance and innovation to highlight some common themes concerning the importance of property rights to economic success. Society regularly makes choices when shaping the precise contours of the legal institutions that govern the behavior of market actors, often in response to high profile issues like the collapse of Enron and the patenting of life-saving AIDS drugs. Recognizing that no set of legal institutions or related enforcement mechanisms will be perfect, this Essay explores some particularly helpful institutional features based on property rights that too often are overlooked by policy makers and commentators, even though these property-based institutional features have long been associated with economic success in a number of diverse settings.
Keywords: Property rights; Institutional economics; Law & economics; Real property; Economic development; Technological innovations; Financial institutions; United States